Effect of proteolytic and detoxification enzyme inhibitors on Bacillus thuringiensis var. israelensis tolerance in the mosquito Aedes aegypti. Issue 2 (1st February 2017) - Hu, Xiaohua; Guo, Yajie; Wu, Songqing; Liu, Zhaoxia; Fu, Tao; Shao, Ensi; Rebeca, Carballar-Lejarazú; Zhao, Guohui; Huang, Zhipeng; Gelbič, Ivan; Guan, Xiong; Zou, Shuangquan; et al.
ABSTRACT: Bacillus thuringiensis var. israelensis (Bti) is highly pathogenic to mosquito larvae and is widely used for mosquito control. Its mosquitocidal activity however is relatively low compared to many chemical insecticides. The detoxification mechanisms in the mosquito, among other things, might neutralize the Bti activity, resulting in resistance or tolerance. We tested whether or not the detoxification mechanisms against chemical insecticides might also operate against Bti, rendering it less effective. We targeted four enzymes in Aedes aegypti larvae involved in detoxification with inhibitors that have been used in resistance studies in chemical insecticides and assayed their effects on Bti toxicity. Results revealed that phenylmethanesulphonyl fluoride (PMSF), diethyl maleate, phenobarbital (PB), and piperonyl butoxide (PBO) altered Bti toxicity to various degrees. PMSF is a serine protease inhibitor that prevents Bti digestion and improves Bti activity. PB that induces several detoxifying enzymes had two different effects depending on the method of treatment. Mortality was higher when treatment with PB was discontinuous (149%) whereas with continuous treatment it was lower (101%). PBO, a typical cytochrome P450 inhibitor, increased Bti effect (159%). The combination of discontinuous pretreatment of larvae with PB followed by PBO had a synergistic effect and showed increased activity (146%). It appears that the mechanism for Bti resistance in mosquitoes is similar to that of chemical insecticides. Our studies indicate that we may be able to increase Bti activity by inhibiting some of the detoxification systems as active as broad spectrum chemical insecticides.